An Empirical Review on the Effects of ICT on the Humanist Thinking - Hermida,Olivia Velarde (2019)
The present article shows the results of a content analysis of scientific publications with two main goals - firstly, it is aimed at identifying the way the implications of ICT in dynamics that impact on the humanisation and dehumanisation of our societies are perceived in scientific publications. The second goal is to check if such representations provide continuity to the humanist thinking existing in the historical periods prior to the emergence of ICT. The content analysis is applied to the identification of narrative structure typologies with different arguments. A total of 136 different types of representations have been identified by applying the Systems Theory designed for the sampling of non-redundant systems. They are analysed with logical and structural methodologies that systemise the representations depending on whether they refer to socio-genetic or anthropo-genetic dynamics. The expected effects are identified, and it is verified that - in most cases - they will be considered both humanising and dehumanising. It is concluded that, as regards to the history of ideas, many humanist representations have continuity - they are still in force because they reflect persistent problems which remain unresolved; and there is a breakdown with the humanist thinking proposed by post-humanisms, which propose genetic and digital interventions that alter human nature.